Latynoscy królowie, nie-żartujący Dominikańczycy i inni transnarodowi braciszkowie: Społeczne i kulturowe implikacje fenomenu band latynoskich w Hiszpanii - Aleksandra Maciuszek (University of Warsaw, Centre of Migration Research (CMR), 2017)
– "Bandas Latinas" - informal youth organizations whose affiliation is based on rootst in the Latin American community along with structures and symbols developed in the USA - appeared in Spain at the beginning of the 21st century and quickly became a symbol of the problems emerging within the context of youth and immigration. The objective of this paper is to provide a multi-aspectual presentation of the phenomenon, in both the aspect of issues involved in the integration of immigrants, as well as of changes occurring in the cultural and self-identification spheres as a result of migration and the existence of transnational networks. The experience of youth in Spain is subjected to continual comparison with that of Latino youth in the USA; the question is also posed of whether the phenomenon of these groups should be viewed in an exclusively negative light. The second chapter contains a presentation of the current state of knowledge on their activities in Spain, confronted with theories concerning integration of the children of immigrants, in particular the idea of segmented assimilation and concepts which emerged out of it. The third chapter addresses the Latin Kings organization - it serves as an example of how "bandas latinas" are created and evolve on three continents, under the influence of diverse factors and with the involvement of various actors. The issue of the dynamics involved in the formation of new markers of identification is raised (the pan-ethnic category of Latino), as well as the role of the culture industry, mass media and the Internet in the forms taken on by the phenomena under discussion; significant space is dedicated to discussion of the theory of imagination proposed by A. Appadurai. Chapter four is devoted to organizations created by youth from the Dominican Republic. They are depicted in the context of transnational studies on migration by Dominicans, particularly their consequences for culture (changes in the understanding of the category of race). The work is rounded out by observations flowing from the analysis conducted of webpages created by members of Dominican "bandas". The concluding chapter is an attempt at systematizing the conclusions appearing in the work, as well as pointing to what may potentially be the most important issues on the plane of migration research raised by the phenomenon of "bandas".
Keywords: 330; integration; identity; 1.5 generation; Latino gangs; new ethnic communities; Spain; Latinos in the USA; Internet; Dominican Republic